Two Stay Two Stray Cooperative Learning on Student Learning Outcomes on Materials of Geometry Surface Area - Desilia Elisabet; Agung Hartoyo; Yulis Jamiah (STKIP Singkawang, 2020)
This study aims to determine whether there is an effect of Two Stay Two Stray cooperative learning on student learning outcomes on the surface area material. The method used in this study is an experimental method with a quasi-experimental form and the research design is Posttest-Only Control Design. The population of this study were all class IX students of SMP Negeri 18 Pontianak for the 2018/2019 academic year which were spread into five classes. The samples of this research were students of class IX D and IX E who were taken by using a simple random sampling technique (simple random sampling). Data collection techniques using measurement techniques and data collection tools with test descriptions used to determine student learning outcomes. After the data was tested in the two samples, the data analysis was then carried out to test the hypothesis. Before the Hypothesis test was carried out, the prerequisite was first tested, namely the Normality Test, because the abnormal normality test, the hypothesis test used the Mann Whitney U-Test. From the results of data analysis, the zcount value was obtained equal to 1.87 while the value of ztable of 1.64 for???? = 0.05. Because of the value of zcount > ztable, it is concluded that there is an effect of cooperative learning Two Stay Two Stray on student learning outcomes.